2015
DOI: 10.5114/pjp.2015.51153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of folic acid on dyslipidemia and serum homocysteine in a rat model of cholestasis and hepatic fibrosis

Abstract: The liver is the major site for storage and metabolism of folate. Folate deficiency is common in many liver diseases and causes severe effects on cellular metabolism and increases oxidative stress and the homocysteine (Hcy) level. The objective of this research was to investigate the effects of folic acid on dyslipidemia and serum Hcy concentrations in an experimental rat model of cholestasis. Eighty-one male Wistar rats were divided into nine groups: control, sham-operated, folic acid control, bile duct-ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…On the other hand, FA increased the bile flow, bile acid synthesis from cholesterol, and bile acid excretion via feces (43). It was suggested that FA is an essential therapeutic intervention in dyslipidemia caused by cholestasis, protecting the liver against cholestasis (44). The enhanced bile synthesis pathway in the liver from the current study confirms the function of FA on bile acid metabolism in sheep.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, FA increased the bile flow, bile acid synthesis from cholesterol, and bile acid excretion via feces (43). It was suggested that FA is an essential therapeutic intervention in dyslipidemia caused by cholestasis, protecting the liver against cholestasis (44). The enhanced bile synthesis pathway in the liver from the current study confirms the function of FA on bile acid metabolism in sheep.…”
Section: Discussionsupporting
confidence: 80%
“…Assay kits for MDA, SOD and GPx were purchased from the Randox (Randox Laboratories Ltd., Crumlin, Antrim, United Kingdom). The dose of FA was obtained from previous studies and our pilot studies 11,12 .…”
Section: Drugs and Detection Kitsmentioning
confidence: 99%
“…Also, curative effect of the FA observed on sperm parameters and oral gavage of the FA (10mg/kg) for 7 days via oral gavage, then subjected to 1 h I/24 h 9 . The doses for FA selected based on the pilot study (un-published data) and previous report 11,12 .…”
mentioning
confidence: 99%
“…These findings suggest that there is an inherent correlation among folate, Hcy and lipid profiles. Additionally, several studies showed that medical nutrition therapy with folate intake significantly reduced serum lipids levels [ 13 , 14 ]. Thus, we speculate that Hcy-metabolism gene polymorphisms associated with folate and Hcy interactively affect the incidence of dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%